MySOMOI: An interdisciplinary platform that promotes wholesome oral health - Arzmi, Mohd Hafiz; Shahdan, Intan Azura (Faculty of Dentistry, University of Malaya, 2018)
The Editor of Annals of Dentistry: Dear Professor, Like many other developing countries, dental caries posed important health problems among children and adults in Malaysia. Lack of awareness on oral health has been suggested as the predisposing factor that might have contributed to dental caries. As a customary practice, oral health promotion is often carried out by dentists themselves, whose practice are regulated by Act 51, Dental Act 1971 -an act that ensures the safety of the patients in the country. However, non-dentists who are working towards promoting good oral health practice are almost scarce or even non-existed at the national level. Moreover, the incidence of a fraud dentist who was caught in 2017 has sent several messages with regards to the level of public awareness on the implications of unqualified dental treatments. The act has since been revised and is now named Act 804, Dental Act 2018.